The Texture of Camel Milk Cheese: Effects of Milk Composition, Coagulants, and Processing Conditions - Mbye, Mustapha; Ayyash, Mutamed; Abu-Jdayil, Basim; Kamal-Eldin, Afaf (Frontiers in Nutrition, 2022)
Numerous people in African, Middle Asian, Middle Eastern, and Gulf Cooperation Council (GCC) countries highly value camel milk (CM) as it plays a vital role in their diet. The protein composition of CM as well as the structure of its casein micelles differs significantly from bovine milk (BM). Cheeses made from CM thus have a fragile and soft texture compared to those made from BM. This review article presents and discusses the effect of milk protein composition, processing conditions (pasteurization and high-pressure treatment), and coagulants (camel chymosin, organic acids, plant proteases) on the quality of CM cheeses. Notable features of CM composition, i.e. the very low κ-casein-to-β-casein ratio (19 in CM versus 3 in BM), large micelle size, different whey protein compositions as well as higher proteolytic activity water retention are factors that contribute to the fragile texture of CM cheese. CM cheese texture can e.g. be improved by preheating the milk at low temperatures or by high-pressure processing. Supplementing CM with calcium has shown inconsistent results on cheese texture, which may be due to interactions with other processing conditions. Despite their soft nature, CM cheeses are generally well-liked in sensory studies.